2009
DOI: 10.1539/joh.l8179
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Stress and Burnout of Lawyers

Abstract: The aim of this study was to explore the associations between burnout and occupational stress measured by demand-control support (DCS) and effort-reward imbalance (ERI) models among lawyers. Methods: This crosssectional study included 180 lawyers from 26 law firms in the Taipei Bar. The Chinese version of Karasek's job content questionnaire (C-JCQ) and the Chinese version of Siegrist's ERI questionnaire (C-ERI) were used to measure occupational stress, and the Chinese version of the Copenhagen Burnout Inventor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
1
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 19 publications
1
37
1
5
Order By: Relevance
“…A survey of a group of nurses in the ORSOSA study in France identified effort/reward imbalance in 10.7% of the nurses and overcommitment in 40.8% of the nurses 19) . Comparisons of the results of the current study with earlier studies of other occupations in Taiwan show effort/reward ratios of 0.74 (0.22) and 0.97 (0.34) in litigious lawyers and healthy engineers, respectively 2,20) . However, the survey of engineers showed a mean overcommitment score of 14.5 ± 5.2 2) .…”
Section: Discussionsupporting
confidence: 61%
“…A survey of a group of nurses in the ORSOSA study in France identified effort/reward imbalance in 10.7% of the nurses and overcommitment in 40.8% of the nurses 19) . Comparisons of the results of the current study with earlier studies of other occupations in Taiwan show effort/reward ratios of 0.74 (0.22) and 0.97 (0.34) in litigious lawyers and healthy engineers, respectively 2,20) . However, the survey of engineers showed a mean overcommitment score of 14.5 ± 5.2 2) .…”
Section: Discussionsupporting
confidence: 61%
“…In a Sino-Japanese joint venture, Chinese employees often work under Japanese management styles, with emphasis on quality and strict operation standards, and experience conflicts arising from cultural differences, which may lead a higher burnout level. Evidence from earlier studies suggested a positive association between burnout and work-related stress 3,16) . However, there has not been any study on the relationship between occupational stress, burnout and turnover intention among employees in Sino-Japanese joint ventures in the literature.…”
mentioning
confidence: 91%
“…Occupational stress is defined as harmful physical and emotional responses incurred in the work environment. With jobs shifting from manufacturing industries to service industries, the psychological and emotional demands of work have increased, which have led to increased attention to work-related burnout 3) . Burnout is a comprehensive concept first proposed by Freudenburger in clinical psychology 4) .…”
mentioning
confidence: 99%
“…Nesta amostra o homicídio ocupou a terceira posição nas causas externas, sendo mais prevalente em número absoluto nos advogados (cinco advogados contra três médicos). Este achado pode ser fundamentado simplesmente pelo maior número de óbitos em advogados em relação aos médicos ou mesmo pela maior exposição profissional dos advogados a situações conflituosas e de risco 29 . Ressalta-se que essa exposição profissional não pode ser generalizada a todos as especialidades de advogados.…”
Section: Materiais E Métodosunclassified